EVALUASI GEDUNG ARSIP POLITEKNIK NEGERI JAKARTA SESUAI SNI 1726-2019 DAN SNI 2847-2019 - Yanuar Setiawan; Bima Ryanto; Mikha Geraldine; Rinawati Rina (Politeknik Negeri Jakarta, 2021)
The purpose of this research is to recalculate the upper structure of the X building of Jakarta State Polytechnic uses SNI-2847-2019 regulations regarding concrete and SNI 1726- 2019regarding earthquakes. This building consists of 3 floors which use concrete as its main structure. Recalculation includes structural elements starting from collar beam, floor plates, beams, and columns, which are expected to withstand the loads who worked on it. Structural analysis was performed using the ETABS 2013 software. Especially for the calculation of the column structure, the SP Column software is used. The results were obtained from the recalculation of the PNJ x Building in the form of dimensional differences and reinforcement against the existing building. Dimension and reinforcement after redesign became more the size of the existing building. The recalculation results indicate that planning re-using SNI 1726-2019 and SNI 2847-2019 are strong to bear the working load after the dimensions and reinforcement are enlarged. Keywords : Structure, Concrete, Dimensions.